Rewilding Play: Design Build Interventions - Susan Herrington; Ivana Lexa-French; Mariana Brussoni (Education Sciences, 2022)
Research on physical interventions installed in outdoor environments and their impacts on children’s play and development is a growing area of study. This paper focuses on the design and installation of outdoor interventions at early childhood education centres in Vancouver, Canada and the impact that theses interventions had on play affordances. With the aim of intervening with inexpensive natural materials and loose parts, graduate students designed, built, and installed interventions and using the Seven Cs evaluation form they scored the play spaces pre- and post-installation. Design methods included the Seven Cs design guidelines and the Two-Eyed Seeing model. Students also sought the insights of Early Childhood Educators, maintenance staff, licensing officers, the British Columbia Cancer Agency, and an Indigenous herbalist/educator. They also examined and addressed solar modifications to create dappled light. To understand the impacts of the student interventions researchers compared the pre- and post-intervention Seven Cs scores, which increased by 20 to 30 points. Researchers seeking to replicate this type of project in their own institutions should carefully consider the impact of climate change on construction timing and material selection, and sensitivity to the diversity of socio-cultural values embedded in the community and within design decisions and the interventions themselves.